Effect of retention features in custom trays on dimensional accuracy of master casts made from alginate impressions - Ramin Mosharraf; Zeynab Zareie (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Complete adhesion of the impression materials to trays is important to prevent impression materials from being pulled away from trays during removed from the mouth and to ensure that the direction of polymerization shrinkage will be towards the tray. The aim of this study was to evaluate the effects of two retention features of custom trays (adhesive vs holes) on the dimensional accuracy of master casts made from two alginate impression materials.Materials and methods: In this in vitro study, 88 impressions were made in eight groups (n=11) of a stainless steel model with three index studs and then poured with a Type III dental stone. Three variables were considered: type of irreversible hydrocolloid material, retentive perforations in impression trays and application of a spray-on tray adhesive. The distances between the reproduced index studs were measured to ±0.01 mm with a digital caliper. Kruskal-Wallis and Mann-Whitney tests, ANOVA and t-test were used for data analysis (α=0.05). Results: ANOVA revealed significant differences between the groups only in the vertical dimension (p value = 0.001). There were significant differences between the two tray and alginate types only in the vertical dimension (p value < 0.001 and p value = 0.011). There were no significant differences between the adhesive and non-adhesive groups. There were significant differences in the means of all the dimensions of the two trays as compared with master model. Iralgin alginate group exhibited significant differences in the means of all the three variables compared to the main cast; Xantalgin alginate exhibited differences only in the longitudinal dimension. Non-adhesive group exhibited significant differences in all the three dimensions but the adhesive group did not reveal significant differences only in the vertical dimension.Conclusion: Perforated tray, Xantalgin alginate and use of adhesive produced more accurate casts in all the dimensions compared to corresponding groups. In cases in which an adhesive is not used dimensional accuracy will improve via perforated trays. By using an adhesive with non-perforated tray, Xantalgin alginate has more accurate results; use of an adhesive along with perforated trays produces better results with Iralgin alginate, but no improvements are achieved with Xantalgin.Key words: Alginates, Dental, Impression Materials, Impression Techniques